Identifikasi Mineral Magnetik Pada Tanah Permukaan Dari Daerah Tercemar Abu Terbang dan Abu Dasar - Sudarningsih Sudarningsih; Fahruddin Fahruddin; Ibrahim Ibrahim; Puji Astuti (Universitas Lambung Mangkurat, 2024)
ABSTRACT. Magnetic susceptibility measurements have been carried out at three points (A1, A2 and A3) on the surface soil around the Asam-asam power plant. This study aims to determine the magnetic minerals that may be present in these soil samples. Magnetic susceptibility measurements were carried out using the Bartington Susceptibility Meter MS2B. Based on the range of susceptibility values in soil samples, it shows the content of magnetic minerals such as ilmenite, pyrrhotites and titanomagnetite which are thought to come from fly ash and bottom ash from combustion at the PLTU.KEYWORDS: magnetic minerals, soil, flying ash, bottom ash